A Self‐Powered Triboelectric Hybrid Coder for Human–Machine Interaction. Issue 3 (27th January 2022) - Cao, Yu; Yang, Yuan; Qu, Xuecheng; Shi, Bojing; Xu, Lingling; Xue, Jiangtao; Wang, Chan; Bai, Yuan; Gai, Yansong; Luo, Dan; Li, Zhou
Abstract: Human–machine interfaces have penetrated various academia and industry fields such as smartphones, robotic, virtual reality, and wearable electronics, due to their abundant functional sensors and information interaction methods. Nevertheless, most sensors' complex structural design, monotonous parameter detection capability, and single information coding communication hinder their rapid development. As the frontier of self‐powered sensors, the triboelectric nanogenerator (TENG) has multiple working modes and high structural adaptability, which is a potential solution for multi‐parameter sensing and miniaturizing of traditional interactive electronic devices. Herein, a self‐powered hybrid coder (SHC) based on TENG is reported to encode two action parameters of touch and press, which can be used as a smart interface for human–machine interaction. The top‐down hollow structure of the SHC, not only constructs a compositing mode to generate stable touch and press signals but also builds a hybrid coding platform for generating action codes in synergy mode. When a finger touches or presses the SHC, Morse code and Gray code can be transmitted for text information or remote control of electric devices. This self‐powered coder is of reference value for designing an alternative human–machine interface and having the potential to contribute to the next generation of highly integrated portable smart electronics. Abstract : A self‐powered hybrid coder (SHC) based on a dual‐mode triboelectric nanogenerator is developed for human–machine interaction. The actions of finger touch and pressing can send a hybrid signal consisting of Morse code and Gray code through the SHC, which has a potential to build a concise multifunctional human machine interface.